Impact of five-cone and ladder drill training on agility among U15 football athletes - Pupuh Harya Prembanyu; Agus Wiyanto; Setiyawan Setiyawan (CV Rezki Media, 2025)
Background: Although it may seem simple, soccer has complex characteristics, which is why many children are attracted to training at soccer schools. Agility is a crucial aspect of the game, as it enables a player to move quickly, evade opponents, and control the ball effectively. At the Pemalang Regency Bina Talenta Soccer School (SSB), agility training is not conducted optimally and has not been implemented systematically with effective methods. Therefore, exercises such as the five-cone and ladder drills need to be implemented to improve player agility more effectively. Objectives: This study aims to examine the impact of five-cone and ladder drill training on the agility of U15 football athletes. Methods: This study used a quantitative descriptive method with a quasi-experimental approach. The experimental design was a pretest-posttest in two groups. The sampling technique used was purposive sampling with 20 players participating in a four-week training program. The instrument to measure agility was the Illinois Agility Test, with a validity level of r = 0.87. The measurement data were analyzed using a difference test with the help of SPSS software version 29.0. Results: The five-cone drill and the ladder drill had a significant effect on agility, as both exercises had a significance value of <0.05. The five-cone drill was more effective than the ladder drill. This was due to the difference in scores between the five-cone drill, which increased by 1.04, and the ladder drill, which increased by 0.84. Conclusions: Both training methods are effective in improving agility and can be integrated into school-based football training programs. Furthermore, the results of implementing these methods can enhance player performance and provide a valuable source of new knowledge for future researchers on agility in SSB players.